The Need for A Cognitive Approach to The Study of Material Culture - Young, David E. (Culture, 1985)
Anthropologists have seldom attempted to bring the study of cognition, behavior, and material culture into a single framework. One way to do this is to view the individual as a cybernetic system in which energy and information circulate among mind, muscles, and the external world. This article reports on the tentative findings of a project which studies the production activities of individual artisans in an attempt to understand how cognitive structures are translated into behavior and how behavioral patterning is reflected in the morphology of artifacts. Implications for anthropological aesthetics and archaeology are examined.